"I Don't Feel Like I Have Any Control of My Life at All . . . Everything Overwhelms Me. Everything": Analyzing Caregiver Uncertainty and Control Through Stance Marking. (October 2019) - Strauss, Susan; Kitt-Lewis, Erin Ann; Amory, Michael
Informal caregivers immersed in the daily care of loved ones at end-of-life stages face such challenges as medical and household issues, worries, doubts, and uncertainties. Using a macro-mezzo-micro approach to discourse, we analyzed parent study interview data involving 46 caregivers facing end-of-life realities. At the mezzo level, we examined caregivers' expressed perceptions of control. We then more finely analyzed discursive expressions of affective stances pertaining to caregivers' emotions and feelings, and epistemic stances pertaining to their knowledge and belief states. Theories of uncertainty and control inextricably interweave areas of cognition, affect, and behavior regarding how caregivers perceive their realities and how they engage in or disengage from coping mechanisms in the process. The findings in this three-tiered approach make salient specific discursive patterns gleaned from systematic and fastidious attention to caregivers' own ways of using language that methodically afford deeper entry into the emotional, physical, and cognitive challenges in their everyday lived experiences.